An Analysis of Wordplay and Idiom Translation in Harry Potter and the Chamber of Secrets into Indonesian - Fauzi, Florence Angelaila; Hamid, Faishal Hamdan Syakirin; Syahid, Abdul; Fauzi, Iwan (The Study Program of English Education of Palangka Raya University, 2025)
This study investigates the translation of wordplay and idioms in Chapter 1 of Harry Potter and the Chamber of Secrets into Indonesian, highlighting the linguistic and cultural challenges inherent in translating creative language. Utilizing Delabastita’s (1993) typology for wordplay and Baker’s (2017) strategies for idioms, the research employs a qualitative comparative method. Findings reveal that wordplay is predominantly paraphrased (66.7%), often resulting in diminished humor and stylistic nuance, while idioms are largely translated literally (55.6%), occasionally producing unnatural phrasing. Nonetheless, successful cultural substitutions—such as rendering “a load of rubbish” as “omong kosong besar”—demonstrate effective dynamic equivalence. The study underscores the tension between maintaining textual fidelity and achieving cultural accessibility, offering practical insights for translators working with fantasy literature and linguistically inventive texts.